2019
DOI: 10.3390/rs11040377
|View full text |Cite
|
Sign up to set email alerts
|

How Groundwater Level Fluctuations and Geotechnical Properties Lead to Asymmetric Subsidence: A PSInSAR Analysis of Land Deformation over a Transit Corridor in the Los Angeles Metropolitan Area

Abstract: Los Angeles has experienced ground deformations during the past decades. These ground displacements can be destructive for infrastructure and can reduce the land capacity for groundwater storage. Therefore, this paper seeks to evaluate the existing ground displacement patterns along a new metro tunnel in Los Angeles, known as the Sepulveda Transit Corridor. The goal is to find the most crucial areas suffering from subsidence or uplift and to enhance the previous reports in this metropolitan area. For this purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…However, in the building area, most average vertical motion rates range from -0.5 to 0.5 mm/yr. Khorrami et al (2019) in their work used 29 Sentinel-1A acquisitions from June 2017 to May 2018 to estimate the deformation rate in Los Angeles between -30 to 10 mm/yr. Vertical movements of the earth's crust occurring in Poland have been studied mainly based on leveling data, which in some works was analyzed together with data from mareograph so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the building area, most average vertical motion rates range from -0.5 to 0.5 mm/yr. Khorrami et al (2019) in their work used 29 Sentinel-1A acquisitions from June 2017 to May 2018 to estimate the deformation rate in Los Angeles between -30 to 10 mm/yr. Vertical movements of the earth's crust occurring in Poland have been studied mainly based on leveling data, which in some works was analyzed together with data from mareograph so far.…”
Section: Discussionmentioning
confidence: 99%
“…Interferometric SAR can detect surface movements with an accuracy of a few millimeters per year and can provide an accurate tool for monitoring of land subsidence, structural damage and underground construction to improve safety and reduce economic loss (ESA Standard Document, 2013). Research that was conducted in various urban areas: Berlin, Leipzig (Haghighi and Motagh, 2017), Rome (Delgado Blasco et al, 2019), London (Bischoff et al, 2019), Paris (Koudogbo et al, 2019) and Los Angeles (Khorrami et al, 2019) have demonstrated the capability and great potential of Sentinel-1A/B (S-1) TOPS, TerraSAR-X and method PSI for monitoring slow deformation, including ground, single buildings and infrastructures. Using the StaMPS algorithm in Berlin, Haghighi and Motagh (2017), determined that from during October 2014 to January 2017 the deformation in the south-eastern part of Berlin was from -4 to 1 mm/yr.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several methods to measure ground deformations, from the most classical ones that involve the calculation of the variations of pore pressures and topographic variations on surfaces, to the most modern techniques including Global Navigation Satellite System (GNSS) and remote sensing methods [31]. Differential Interferometric Synthetic Aperture Radar (DInSAR) is a remote sensing technology that can provide high resolution, day and night, weather independent, wide-coverage, and high accuracy measurements of the earth's surface changes [32]. Thus, this technique can detect and monitor regional-scale surface subsidence at low cost with centimeter to millimeter accuracy [9,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Differential Interferometric Synthetic Aperture Radar (DInSAR) is a remote sensing technology that can provide high resolution, day and night, weather independent, wide-coverage, and high accuracy measurements of the earth's surface changes [32]. Thus, this technique can detect and monitor regional-scale surface subsidence at low cost with centimeter to millimeter accuracy [9,[32][33][34][35]. DInSAR has been used to study settlements as a consequence of groundwater withdrawal around the world, especially in places where the population mostly depends on groundwater reserves, and as a consequence the exploitation of the available aquifers has taken place.…”
Section: Introductionmentioning
confidence: 99%
“…The papers related to PSI describe methodological and application-oriented research work. In reference [8], the authors assess the deformations associated with the construction of a new metro tunnel. In reference [9], PSI results are used as a key input for geological and geomorphological analyses in urban areas.…”
mentioning
confidence: 99%